Painting the inhabited landscape : Fitz H. Lane and the global reach of antebellum America - Lovell, Margaretta M. (The Pennsylvania State University Press, 2023)
"Examines landscape, harborscape, and seascape paintings by Fitz H. Lane (1804-1865) that comment on agriculture, extraction industries, settlement patterns, trade, and the political economy of nineteenth-century coastal New England"--